Human performance measures for the evaluation of process control human-system interfaces in high-fidelity simulations. (November 2018) - Xu, Jie; Anders, Shilo; Pruttianan, Arisa; France, Daniel; Lau, Nathan; Adams, Julie A.; Weinger, Matthew B.
Abstract: We reviewed the available literature on measuring human performance to evaluate human-system interfaces (HSIs), focused on high-fidelity simulations of industrial process control systems, to identify best practices and future directions for research and operations. We searched the available literature and then conducted in-depth review, structured coding, and analysis of 49 articles, which described 42 studies. Human performance measures were classified across six dimensions: task performance, workload, situation awareness, teamwork/collaboration, plant performance, and other cognitive performance indicators. Many studies measured performance in more than one dimension, but few studies addressed more than three dimensions. Only a few measures demonstrated acceptable levels of reliability, validity, and sensitivity in the reviewed studies in this research domain. More research is required to assess the measurement qualities of the commonly used measures. The results can provide guidance to direct future research and practice for human performance measurement in process control HSI design and deployment. Highlights: Human performance measures in process control HSI evaluation were reviewed. The reviewed measures were categorized into six human performance dimensions. Many of the measures were not adequately evaluated in the reviewed domain. We provided recommendations on current practices and future directions.